Balanced Nutrition and Healthy Menu Based Training Local Food during the COVID-19 Pandemic for Posyandu Cadres in Batu Merah Village: Pelatihan Gizi Seimbang dan Menu Sehat Berbasis Pangan Lokal Masa Pandemi COVID-19 pada Kader Posyandu di Desa Batu Merah - Martha Puspita Sari; Khartini Kaluku; Mahmud Mahmud (Universitas Lancang Kuning, 2023)
SARS-Cov-2 is a new virus that causes respiratory diseases that can cause health problems. Consuming foods with balanced and safe nutrition can boost the immune system and reduce the risk of disease.Community service through a community partnership program is carried out by implementing balanced nutrition training using booklets and balanced nutrition cards in Batu Merah Village. The training participants were 15 Dahlia Posyandu cadres in Batu Merah Village. Booklets as a communication medium for health education can increase the average knowledge and attitudes of mothers about choosing healthy and nutritious food. This activity adds insight into the participants' thinking that being healthy is not always expensive, but it can be realized by consuming a variety of foods that are cheap and easy to obtain practical and can be applied every day.